2023
DOI: 10.3390/biomedicines11020304
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hyaluronic Acid in Selected Malignant Neoplasms in Women

Abstract: Hyaluronic acid (HA) is a significant glycosaminoglycan component of the extracellular matrix, playing an essential role in cell localization and proliferation. However, high levels of HA may also correlate with multidrug resistance of tumor cells, an increased tendency to metastasize, or cancer progression, and thus represent a very unfavorable prognosis for cancer patients. The purpose of this review article is to summarize the results of studies describing the relationship between HA, the main ligand of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…Hyaluronic acid (HA) is another popular biomaterial most commonly used post-operatively, particularly in the form of a hydrogel, and can be combined with both natural molecules as well as synthetic polymers (Abatangelo et al, 2020). However, care must be taken when using HA, as it has been shown to regulate the TME and promote the malignant phenotype of cancer cells, and lead to multidrug resistance (Markowska et al, 2023). So, whilst HA is beneficial in applications such as wound repair, studies have shown that it can also effectively feed the cancer, causing it to grow and spread.…”
Section: Biomaterial-based Scaffoldsmentioning
confidence: 99%
“…Hyaluronic acid (HA) is another popular biomaterial most commonly used post-operatively, particularly in the form of a hydrogel, and can be combined with both natural molecules as well as synthetic polymers (Abatangelo et al, 2020). However, care must be taken when using HA, as it has been shown to regulate the TME and promote the malignant phenotype of cancer cells, and lead to multidrug resistance (Markowska et al, 2023). So, whilst HA is beneficial in applications such as wound repair, studies have shown that it can also effectively feed the cancer, causing it to grow and spread.…”
Section: Biomaterial-based Scaffoldsmentioning
confidence: 99%
“…Hyaluronic acid (HA) is a naturally occurring polymer and a glycosaminoglycan component of the extracellular matrix [ 171 ]. Overexpression of HA could indicate a poor prognosis, as it could be involved in progression, metastasis, and multidrug resistance [ 172 ]. A meta-analysis of breast cancer cases shows a correlation between high HA levels and lower disease-free survival, recurrence-free survival, and progression-free survival rates [ 173 ].…”
Section: The Unchartedmentioning
confidence: 99%
“…The extracellular matrix (ECM) of soft connective tissues contains the highest levels of HA in the human body. Intracellular adhesion molecule (ICAM-1), cluster determinant 44 (CD44), and the receptor for hyaluronate-mediated motility (RHAMM) are a few examples of HA-specific receptors [18].…”
Section: Introductionmentioning
confidence: 99%